Relationship between age-sex classes and prevalence of Giardia spp. and Blastocistys spp. in black and gold howler monkeys inhabiting fragmented forests - Alegre, Rumesilda Eliana; Gennuso, María Sol; Milano, Francisca; Kowalewski, Martin (THERYA, 2021)
Studies have shown that as age increases, parasitism could also be more frequent, on the other hand, the lack of immunity can increase the risk of infection in younger individuals. Regarding sex, there is a general tendency for males to be more parasitized than females, in the case of primates, this is related to the effort made by males into attaining and maintain a high rank, implying high levels of testosterone, a hormone with immunosuppressive effects. Immunosuppressive effects of stress hormones can also increase susceptibility in dominant or subordinate individuals, nevertheless, in a study, the level of exposure to parasites seems to be more important than the immunosuppressive effects of stress in explaining why dominant females have more infections from directly transmitted parasites. In this study, we investigated the relationship between the prevalence of Giardia spp. and Blastocystis spp. and the categories of age and sex in black and golden howler monkeys (Alouatta caraya) of Argentina. We analyzed 375 fecal samples from 27 individuals (juveniles and adults of both sexes), using microscopy and techniques of flotation and sedimentation. To analyze the relationship between age, sex, and infection prevalence, a Generalized Linear Mixed Model was used. In adults, the prevalence of infection was 78.5 % while in juveniles, all individuals (100 %) were infected with both protozoa. Males had a infection prevalence 84.6%, in females it was 92.8 %. When comparing infection prevalence between ages and between sexes, no significant differences were found (P > 0.05). Research suggests that parasite infection rates may be influenced by specific form of transmission, in this sense, these protozoa, are transmitted through ingestion of cysts which are infectious immediately after defecation has occurred. On the other hand, all members of the group tend to defecate simultaneously, leaving all the members of the group exposed to infection. Therefore, we suggest that physiological or behavioral factors do not appear to be important in the risk of protozoan infection.